PENGARUH BRAND AWARENESS, BRAND ASSOCIATION DAN FAKTOR PSIKOGRAFIS TERHADAP KEPUTUSAN PEMBELIAN ETUDE HOUSE DI SEMARANG - Sandy Salsabila Khaerunissa; Bulan Prabawani; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
Along with the development of science and technology, human needs are becoming increasingly complex. Not just a case of trying to meet the basic needs of food, clothing, home and education, but also the physical appearance and beauty treatments (both face and body) has become a top priority and regarded as a necessity that must also be met, especially women. This is why cosmetics and skin care products are sought after by women to beautify the appearance.Value turnover cosmetic industry in Indonesia has increased. One of the countries that are aggressively marketing in cosmetics is South Korea, which launched the brand named Etude House. Etude House increase Brand Awareness by expanding the store and entered into malls in major cities, therefore it can arised Brand Associations that can create an impression of the product. Besides Brand Awareness and Brand Association, Psychographic Factors also include in process of purchasing products Etude House. Psychographic Factors refers to the lifestyle of make up that was transmitted through the Korea through Etude House                 In this final assignment, the effect of Brand Awareness, Brand Association and Psychographic Factors in decision to buy Etude House is determined. Data collection technique used is purposive sampling with 100 sample. The data is analyzed through validity test, reliability test, crosstab, product moment correlation, coefficient of determination, simple linear regression, multiple linear regression, t-test and F-test. The data is analyzed quantitatively using the SPSS program version 15.The results showed that Brand Awareness have not a significant influence in decision to buy Etude House in Semarang partially. However, Brand Association and Psychographic Factors have a significant influence in desicion to buy Etude House in Semarang partially. Brand Awareness, Brand Association and Psychographic Factorsalso have a significant influence in decision to buy Etude House in Semarang simultaneously.Etude House Brand Awareness should be increased through the identical color, logo, brand ambassador and the packaging, so consumers can be aware of the existence of Etude House. Improvement can be done with the addition of the logo on any product, promotion through print or electronic media with brand ambassador of the famous Korean artists. Moreover, imrpoved a good quality, although the price is quite expensive, if the brand gave a good quality will encourage consumers to buy products Etude House .